RELATIONSHIP BETWEEN OXIDATIVE STRESS AND NEUTROPHIL APOPTOSIS INTENSITY IN TRAUMATIC CRANIAL INJURY ASSOCIATED WITH DIABETES - Meretskyy, V.M.; Korda, M.M. (World of Medicine and Biology, 2013)
Investigated the relationship between the degree of oxidative stress in blood neutrophils and the intensity of neutrophil apoptosis in experimental traumatic cranial injury against streptozotocin-induced diabetes. It is established that trauma is characterized by a sharp increase in production of reactive oxygen species, an increase in the number of annexin V positive cells, which reaches its maximum on the 5th day of observation, and the fraction of white blood cells positive for propidium iodide, especially in the period of the early manifestations of the injury. Concomitant diabetes mellitus leads to a more pronounced increase in the phenomena of apoptosis and free radical oxidation in neutrophils. It is concluded that the head injury, diabetes, and especially when cranial injury and diabetes mellitus increases the intensity of neutrophil apoptosis. The activity of apoptosis correlated with the degree of oxidative stress in neutrophils.